Rancang Bangun Sistem Informasi Penerimaan Keuangan Sekolah Berbasis Client Server di SMK Pasundan Jatinangor - Irma Rahmawati Malik; Utami Aryanti (Ma'soem University, 2023)
This Client Server-Based School Financial Receipt Information System Design was developed to make it easier for teachers' school financial receipt transactions at SMK Pasundan Jatinangor so as to minimize duplication. This Client Server-Based School Financial Receipt Information System Design uses the SDLC (system Development Life cycle) system development method starting from the system development process until the system is implemented, which consists of several basic work stages, including analysis (Analysis), Design (Design). ), Code (Coding), Testing, and maintenance, with the waterfall model. While the research methodology used is descriptive method, to obtain data using observation, interviews, literature studies, and documentation studies. In optimizing the design of the school financial acceptance information system, using tools such as Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), Flowmaps, Structured Charts and Data Dictionary. Hopefully this program can help to overcome the problems and risks encountered in the system that was running previously and will make it easier for users to make decisions